Taking angiotensin-converting enzyme inhibitors during pregnancy: Is it safe? - Al-Maawali, Almundher (College of Family Physicians of Canada, 2012)
Question One of my 35-year-old pregnant patients has been treated with enalapril for primary hypertension. She learned she was pregnant at 11 weeks’ gestation. I read somewhere that angiotensin-converting enzyme (ACE) inhibitors can cause malformations. What advice do you give to Motherisk callers? Answer Most published studies have failed to show an effect of ACE inhibitors on congenital malformations. A recent systematic review and meta-analysis conducted by Motherisk does not suggest increased fetal risk of malformations. However, ACE inhibitors should be avoided in late pregnancy, as they might cause renal failure and acalvaria in the baby.